First molecular detection and genetic analysis of porcine circovirus 4 in the Southwest of China during 2021–2022 - Xu, Tong; You, Dong; Wu, Fang; Zhu, Ling; Sun, Xian-Gang; Lai, Si-Yuan; Ai, Yan-Ru; Zhou, Yuan-Cheng; Xu, Zhi-Wen (Frontiers in Microbiology, 2022)
Abstract: Porcine circovirus 4 (PCV4) was identified in 2019 as a novel circovirus species and then proved to be pathogenic to piglets. However, there is a lack of its prevalence in the Southwest of China. To investigate whether PCV4 DNA existed in the Southwest of China, 374 samples were collected from diseased pigs during 2021-2022 and detected by a real-time PCR assay. The results showed that the positive rate of PCV4 was 1.34% (5/374) at sample level, and PCV4 was detected in 2 of 12 cities, demonstrating that PCV4 could be detected in pig farms in the Southwest of China, but its prevalence was low. Furthermore, one PCV4 strain (SC-GA2022ABTC) was sequenced in this study and shared a high identity (98.1-99.7%) with reference strains at the genome level. Combining genetic evolution analysis with amino acid sequence analysis, three genotypes PCV4a, PCV4b and PCV4c were temporarily identified, and the SC-GA2022ABTC strain belonged to PCV4c with a specific amino acid pattern (239V for Rep protein, 27N, 28R and 212M for Cap protein). Phylogenetic tree and amino acid alignment showed that PCV4 had an ancient ancestor with mink circovirus. In conclusion, the present study was the first to report the discovery and the evolutionary analysis of the PCV4 genome in pig herds of the Southwest of China and provide insight into the molecular epidemiology of PCV4.